1989
DOI: 10.1016/0741-5214(89)90467-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of saphenous vein patch, polytetrafluoroethylene patch, and direct arteriotomy closure after carotid endarterectomy. Part I. Perioperative results

Abstract: To evaluate the perioperative outcomes and the immediate increases in size after patch closure, 140 carotid endarterectomies were randomized into one of three groups: direct no-patch closure, saphenous vein patch closure, and polytetrafluoroethylene patch closure. Seven patients (4.4%) experienced signs of cerebral ischemia in the immediate postoperative period. In three cases this was transient and reversible. In the other four reexploration was undertaken and carotid thrombosis was corrected by thrombectomy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Miyamotto et al, in 2009, in an experimental study comparing bovine pericardium patch with greater saphenous vein patch, concluded that the bovine pericardium patch had a higher rupture resistance than that observed in the greater saphenous vein group. Lord et al, in 1989, reported that PTFE patches, when used after carotid endarterectomy, resisted dilatation better than saphenous vein patches. In this study, dilatation was observed in 9.23% of the PTFE patches and in 17% of the saphenous vein patches.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Miyamotto et al, in 2009, in an experimental study comparing bovine pericardium patch with greater saphenous vein patch, concluded that the bovine pericardium patch had a higher rupture resistance than that observed in the greater saphenous vein group. Lord et al, in 1989, reported that PTFE patches, when used after carotid endarterectomy, resisted dilatation better than saphenous vein patches. In this study, dilatation was observed in 9.23% of the PTFE patches and in 17% of the saphenous vein patches.…”
Section: Discussionmentioning
confidence: 98%
“…Menon et al, in 1973, in an experimental study performed on dogs, reported only one case of dilation in 30 Dacron patch angioplasties over the abdominal aorta and carotid and femoral arteries. 23,[28][29][30] The time of clinical observation in the experimental studies using patches has been varied. The time course used in this study to evaluate the patches was the same reported by Sarac et al in 2006, when they described the efficacy of bovine peritoneum/fascia patches in femoral artery angioplasty on dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamically significant recurrent stenosis rates of 5% to 7% have been reported in multicenter trials (62,176,276,(282)(283)(284)(285)(286)(287)(288)(289)(290)(291)(292)(293)(294)(295)(296)(297)(298)(299). Data comparing restenosis after CEA and CAS must be interpreted cautiously because of selection bias and stentgenerated artifacts in ultrasound velocity measurements.…”
Section: Durability Of Carotid Revascularizationmentioning
confidence: 94%
“…Results from a number of trials are available comparing CEA using vein from different sources or synthetic patch (PTFE or Dacron) [42][43][44][45][46][47]. Even though more than 1200 patients were included in these studies and reviewed in two systematic reviews [41,48], the presented data were still insufficient to firmly recommend one type of patch over the other.…”
Section: Postoperative Cerebral Ischemic Events and Restenosismentioning
confidence: 88%